Different Responses of Chlorophyll a to the Passage of the Tropical Storm Wipha (2019) in the Coastal Waters of the Northern Beibu Gulf - Chen, Ying; Ren, Chaoxing; Feng, Yuting; Shi, Haiyi; Pan, Gang; Cooper, Mick; Zhao, Hui (Frontiers in Marine Science, 2022)
Tropical storm (TS) is an important driver of short-term changes and affects the coastal and marine environment. Based on in situ observational data from 4 locations in the coastal area of the northern Beibu Gulf and satellite data, we analyzed the changes in temperature, salinity, and turbidity during the transit of TS "Wipha" in 2019 and assessed the environmental factors controlling chlorophyll a concenteation (Chl-a) increases in the coastal area. Our results showed that in the coastal area, the growth of phytoplankton after the TS was mainly controlled by the nutrient and light availability. The increased input of freshwater by TS, including direct inputs from rainfall and increased river discharge, reduced the salinity. The decrease in salinity may indicate an increased input of nutrient-rich freshwater at all 4 stations (nutrients input: S1>S2>S3>S4). Nutrients concentration at S1, S2, and S3 implied by salinity was high, but that at S4 was limited. The shorter recovery time of turbidity after TS indicated the faster improving of light conditions better in this area [recovery time: S4 (2 days)< S1 (3 days)< S3 (5 days)< S2 (10 days)]. The high turbidity associated with poor light penetration was an important factor limiting phytoplankton growth at station 2, with a slow recovery of the turbidity to pre-TS levels. The rapid recovery of the turbidity to the pre-TS levels at S1, S3, and S4 suggested good light conditions soon after the TS, and probably led to a significant increase in Chl-a after the TS ([Chl-a]: S1>S3>S4). The less increase of Chl-a at S4 was not only related to nutrient restriction, but also related to weak mixing of water column, while the least significant decrease in the SST at S4 implied that the enhancing mixing after TS was limited.